2013
DOI: 10.1016/j.ijsu.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications in the oldest old gastric cancer patients

Abstract: Patients over 85 years old are more likely to suffer postoperative pneumonia after gastrectomy than younger old patients. Preoperative risk assessment is essential for the oldest old patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
3
28
1
Order By: Relevance
“…Kunisaki et al reported that the frequency of pneumonia differed significantly between patients aged 45-65 and those aged ≥75 years (6.3 vs. 13.3 %, respectively) [6]. Moreover, Yamada et al reported that the frequency of pneumonia was significantly higher in patients aged ≥85 years than in those aged 75-84 years (16.7 vs. 3.3 %, respectively) [8]. The results of these two studies show that the risk of pneumonia increases with age, consistent with our findings, although these previous studies did not focus solely on postoperative pneumonia and did not perform multivariate analysis to identify risk factors for postoperative pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kunisaki et al reported that the frequency of pneumonia differed significantly between patients aged 45-65 and those aged ≥75 years (6.3 vs. 13.3 %, respectively) [6]. Moreover, Yamada et al reported that the frequency of pneumonia was significantly higher in patients aged ≥85 years than in those aged 75-84 years (16.7 vs. 3.3 %, respectively) [8]. The results of these two studies show that the risk of pneumonia increases with age, consistent with our findings, although these previous studies did not focus solely on postoperative pneumonia and did not perform multivariate analysis to identify risk factors for postoperative pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the cutoff for the definition of "elderly" patients. Various cutoffs have been used for defining elderly patients [7]; however, as a cutoff of 75 years has been used recently in many reports [6,8], we used this cutoff in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency of pneumonia after gastrectomy in elderly patients aged ≥75 years has been reported as 5.1‐13.3%, which is significantly higher than that of younger patients (ie 45‐65 years old) . Pneumonia developed in 12.8% of the present patients, which is similar to findings of previous studies, but advanced age (≥80 years) did not increase the incidence of pneumonia in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…29 In a study by Yamada et al, wherein the elderly group was defined as being 85 years and above, ASA grade, CCI, forced expiratory volume at 1 second (FEV1) and serum albumin concentration correlated with the occurrence of postoperative pneumonia. 30 Tran et al reported that age (≥ 80 years defined as elderly), blood transfusion, serum albumin and creatinine were independent predictors of 90-day mortality rate and tumour stage. Tumour grade, race, blood transfusion and adjuvant therapy were independently associated with disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%